Math, asked by sheelaukade, 6 months ago

In the expansion of (x + 3) (x + 2), what will be the middle term.​

Answers

Answered by olimpica111
2

Answer:

Given, (1−3x+3x

2

−x

3

)

2n

=[(1−x)

3

]

2n

=(1−x)

6n

Middle term =

2

N

+1

=

2

6n

+1

=(3n+1)

th

term

Now consider the following,

T

r+1

=

n

C

r

a

n−r

b

r

...(i)

Where T represents the term

Here the middle term is the (3n+1)

th

term.

Hence, r+1=3n+1

r=3n

Substituting in (i), we get

(−1)

3n

6n

C

3n

1

6n−3n

x

3n

=(−1)

3n

6n

C

3n

x

3n

=

6n

C

3n

(−x)

3n

Answered by KomalThengri
0

Step-by-step explanation:

(x + 3)(x + 2) = x(x + 2) + 3(x + 2) \\  =  {x}^{2}  + 2x + 3x + 6 \\  =  {x}^{2}  + 5x + 6

hence , the middle term of the expression is 5x

Similar questions